Implementasi Supervisi Pendidikan dalam Meningkatkan Proses Pembelajaran di Sekolah - Subandi Subandi; Nandha Rahayu; Paundra Raditya Khoidori (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
One of the strategic efforts to improve the quality of learning in schools is educational supervision. This study examines how to implement educational supervision to improve learning. Educational supervision includes classroom observation, professional teacher guidance, performance evaluation, and providing constructive criticism. The research methods used include in-depth interviews with principals, teachers, and school supervisors. The results of the study indicate that teachers can improve their pedagogical skills, create a more interactive learning atmosphere, and improve student learning outcomes with effective supervision. Effective supervision also helps teachers create different learning methods that are in accordance with student needs. Therefore, educational supervision plays an important role in building a good learning culture in schools.